A Mouse Model of Beta-Cell Dysfunction as Seen in Human Type 2 Diabetes - Jacqueline H. Parilla; Joshua R. Willard; Breanne M. Barrow; Sakeneh Zraika (Journal of Diabetes Research)
Loss of first-phase insulin release is an early pathogenic feature of type 2 diabetes (T2D). Various mouse models exist to study T2D; however, few recapitulate the early β-cell defects seen in humans. We sought to develop a nongenetic mouse model of T2D that exhibits reduced first-phase insulin secretion without a significant deficit in pancreatic insulin content. C57BL/6J mice were fed 10% or 60% fat diet for three weeks, followed by three consecutive, once-daily intraperitoneal injections of the β-cell toxin streptozotocin (STZ; 30, 50, or 75 mg/kg) or vehicle. Four weeks after injections, the first-phase insulin response to glucose was reduced in mice when high-fat diet was combined with 30, 50, or 75 mg/kg STZ. This was accompanied by diminished second-phase insulin release and elevated fed glucose levels. Further, body weight gain, pancreatic insulin content, and β-cell area were decreased in high fat-fed mice treated with 50 and 75 mg/kg STZ, but not 30 mg/kg STZ. Low fat-fed mice were relatively resistant to STZ, with the exception of reduced pancreatic insulin content and β-cell area. Together, these data demonstrate that in high fat-fed mice, three once-daily injections of 30 mg/kg STZ produces a model of β-cell failure without insulin deficiency that may be useful in studies investigating the etiology and progression of human T2D.